Anticancer Therapies Based on Oxidative Damage: Lycium barbarum Inhibits the Proliferation of MCF-7 Cells by Activating Pyroptosis through Endoplasmic Reticulum Stress - Miranda, Maria Rosaria; Basilicata, Manuela Giovanna; Vestuto, Vincenzo; Aquino, Giovanna; Marino, Pasquale; Salviati, Emanuela; Ciaglia, Tania; Domínguez-Rodríguez, Gloria; Moltedo, Ornella; Campiglia, Pietro; Pepe, Giacomo; Manfra, Michele (Antioxidants, 2024)
Lycium barbarum, commonly recognized as goji berry or wolfberry, is highly appreciated not only for its organoleptic and nutritional properties but also as an important source of bioactive compounds such as polysaccharides, carotenoids, phenolics, and various other non-nutritive compounds. These constituents give it a multitude of health benefits, including antioxidant, anti-inflammatory, and anticancer properties. However, the precise biochemical mechanisms responsible for its anticancer effects remain unclear, and the comprehensive composition of goji berry extracts is often insufficiently explored. This study aimed to investigate the biochemical pathways modulated in breast cancer cells by an ethanolic extract of Lycium barbarum fruit (LBE). Following metabolomic profiling using UHPLC-HRMS/MS, we assessed the antitumoral properties of LBE on different breast cancer cell lines. This investigation revealed that LBE exhibited cytotoxic effects, inducing a pro-oxidant effect that triggered pyroptosis activation through endoplasmic reticulum (ER) stress and subsequent activation of the P-IRE1α/XBP1/NLRP3 axis in MCF-7 cells. In addition, LBE did not display cytotoxicity toward healthy human cells but demonstrated antioxidant properties by neutralizing ROS generated by doxorubicin. These findings underscore the potential of LBE as a highly promising natural extract in cancer therapy.